Education Sector Strategy During COVID-19 Pandemic In Indonesia: Policy Transition To Face-To-Face Learning - Muhammad Nurdin Alamsyah; Muhamad Azami Nasri; Siti Ghina; Krisna Puji Rahmayanti (Aliansi, 2022)
This study explores the strategy of the Government of Indonesia in conducting face-to-face learning in the second year of the COVID-19 pandemic and investigates its effectiveness. The government finally implemented a face-to-face learning policy for elementary to high school students in 2021 in response to the decline of the COVID-19 confirmed cases in the country. Still, this policy has implications for the emergence of a new COVID-19 cluster that threatens children, as happened in the increasing number of children affected by COVID-19 from 13% in July 2021 to 15% in August 2021 children were infected. This research conducts a desk review and content analysis of policies related to face-to-face learning strategies. The result finds that the government has made policy transitions since the COVID-19 pandemic emerged from online learning policies to gradual face-to-face learning involving various national and local actors playing a crucial role in the implementation of face-to-face learning. The policy implementations face several obstacles, such as the lack of readiness of school infrastructure and the disparity of the community literacy toward COVID-19 pandemic include students and parents. This study concludes that the government adapts to the COVID-19 pandemic development in developing education sector strategies but still requires necessary improvements. This study reveals that face-to-face learning strategies are required to create a new strategy that applies to all students and schools, improve existing school health infrastructure, and conduct socialization activities related to face-to-face learning.